Active and reactive power control of hybrid offshore AC and DC grids. (2nd October 2019) - Raza, Muhammad
Abstract : The future 'SuperGrid' may requires the benefit of both offshore AC network and multi-terminal DC grid. AC cable limits the power transfer capability from the larger offshore wind farm, however, HVDC transmission system is economical viable for large power wind farm integration with the grid. Another approach to develop the offshore network infrastructure is by forming an offshore AC grid connecting several offshore wind farms. Then, this offshore AC network is connected with different onshore grid using HVDC system. This enhances the trade among the countries as well as provide an economical solution for wind energy integration. In this article, operational and control concept of voltage source converter is presented to integrate an offshore AC grid with an offshore DC grid. The article presents the control principle of offshore AC network frequency and voltage with respect to active and reactive power distribution in the AC network. Later, the principle of multi-terminal HVDC system is discussed with respect to power distribution using DC voltage droop control. Power distribution criteria are defined with respect to operator power-sharing requirement and network stability. In the end, a hybrid AC/DC offshore grid is modelled and simulated in MATLAB/SIMULINK to validate the distribution criteria.